Minat Wisatawan terhadap Makanan Lokal Kota Semarang - Rahma, Neily; Susilowati, Indah; Purwanti, Evi Yulia (UI Scholars Hub, 2017)
Currently, culinary tourism is potential to be developed as one of the leading tourism. One of the cities in Central Java that has become culinary tourism icon is Semarang. The diversity of ethnic and tribe produces variety of local food and culinary destination to attract tourists. This research aims to know the difference of tourist behavior in Semarang based on age and marital status groups. This research using descriptive statistics with crosstab and analysis of variance (ANOVA). Based on the results of the One Way ANOVA, there are significant differences of authentic experience and prestige on respondents based on age group; and significant differences of authentic experience, exiting experience, health concern, prestige, and togetherness on respondents based on marital status groups.